Planning and Design of the Automotive Engineering Building of SMKN 2 Surakarta with Green Architecture Concept - Wahyu Noviansyah; Amanda Putri Thalia; Chundakus Habsya; Adhan Efendi (Jurnal Pendidikan Teknik Sipil, 2024)
Background: The Automotive Engineering Department of SMKN 2 Surakarta has a problem with a lack of classrooms, unmet standards of space area and height, and problems of glare and heat in the room caused by wide ventilation but no canopy or coating walls. Based on the Guidelines for the Standardization of High School Buildings and Furniture, the infrastructure that is met, the building requirements, and the provisions that are applied greatly affect student learning. Space, air circulation, natural and artificial lighting are related to the performance of teachers and learners.Methods: This planning and design uses the architectural programming method with a green architecture approach. The stages of architectural programming include: determining goals, collect fact, uncover and test concepts, determining needs, and design. Data sources were taken from informants, archives, and documents. Data collection was conducted using observation, interview, and documentation techniques.Results: Space requirements in the Automotive Engineering Department include classrooms, teachers' rooms, basic automotive workshops, material tool rooms, toolman rooms and toilets. The application of green architecture principles includes conserving energy by utilizing solar panels, utilizing gray water, using brightly colored paint; working with climate by utilizing natural lighting and air conditioning, skylight applications, cross ventilation; respect for site through site shape adjustments; respect for use through calculating the area of space according to standards, installing roster walls and vegetation, minimizing new resources related to conserving energy; and holistic.Conclusion: The Automotive Engineering Building consists of two masses, namely the two-story main building (12 classrooms, 1 teacher's room, 4 toilets) and the one-story basic automotive workshop building (1 practice room, 2 toilets, 1 tool and material room and toolman room). The opening area for natural lighting and ventilation is 17-20% following the opening area guideline of 10-20% of the floor area. The use of solar panels as an effort to save energy produces a power of 9,500 WP which can meet the power needs of 9,262.56 WP. The management of gray water which can then be used to flush toilets is 4,645.2 L/day (33%) of the water demand of 13,974 L/day (100%).